PENGARUH TEKNIK KOLASE 4M TERHADAP PERKEMBANGAN MOTORIK HALUS PADA ANAK USIA PRASEKOLAH 4-6 TAHUN DI RW 07 KECEMATAN PURWODADI (STIKES Telogorejo Semarang, 2024)
Preschool age children are children with an age range of 4-6 Children at this age show further motor development and show the ability to move more activities. The 4M collage technique activity is an activity where children can learn to write, cut, stick and fold using a child's fingers, from these small movements that can provide a stimulus or stimulation in children's fine motor development because 4M collage technique activities require eye-muscle coordination. - finger muscles, so that children's fine motor development develops optimally. The design in this study used a quasi-experimental design using a one group pre-post test design, with a total sample of 38 respondents. Data collection using the observation sheet Denver II to determine fine motor development before being given the 4M collage technique. To find out the difference before and after the 4M collage technique, the researcher used the test analysis Wilcoxon. With the results showing a p value of 0.000 0.05, it can be concluded that there is an influence of the 4M collage technique on the fine motor development of preschool children aged 4-6 years in Rw 07 Purwodadi District. Recommendations from this study are teachers can add learning activities using collage techniques as a stimulation for fine motor development of preschool children.